OPTICAL PROBE APPARATUS (2004)
PROBLEM TO BE SOLVED: To provide an optical probe apparatus capable of displaying a proper image even if movement, or the like, is generated in the case of high magnification observation. SOLUTION: A subject is irradiated with light having a low coherence and the coherent component of the return light from the subject is photoeletrically converted by a photodetector 28. An image parameter is extracted from the converted coherent component by an image parameter extraction means 41 through an analogue signal processing circuit 31. The signal converted to a digital signal is subjected to a proper contrast conversion using the image parameter necessary for contrast conversion by a contrast conversion means 39 in a PC (programmable control) 36. This signal is converted to a proper image by a multi-image display means 40 to be utilized in real time display or the display or preservation of only an image, the contour of which is detected at a set level or more. COPYRIGHT: (C)2004,JPO